The Strategic Role of Islamic Education Teachers in Addressing Student Insecurity: A Case Study at SMP Daarul Aitam - Zulhijra Zulhijra; Syarnubi Syarnubi; Aisha Ã–zkan; Abdan Rahim (SYAMIL: Journal of Islamic Education, 2025)
Low self-esteem among adolescents is a critical issue that directly impacts academic, social, and spiritual development. In the context of Islamic education, Islamic Religious Education (IRE) teachers hold a strategic position in helping students build self-confidence and psychological resilience. This study aims to analyze the Islamic pedagogical strategies employed by IRE teachers in addressing students' low self-esteem at SMP Daarul Aitam Palembang. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation. Research informants consisted of PAI teachers, class advisors, and students selected purposively until data saturation was achieved. Data analysis was conducted using thematic analysis techniques. The research results identified three main roles of PAI teachers: (1) as educators who instill Islamic values through tadabbur Al-Qur'an and internalization of Islamic self-concept; (2) as mentors who provide emotional guidance and informal counseling based on a spiritual approach; and (3) as role models (uswah hasanah) in religious behavior that builds a supportive environment. These findings emphasize the importance of integrating Islamic pedagogy in shaping students' character and psychological well-being. It is recommended that PAI teachers receive adolescent psychology training based on Islamic values to strengthen character education in Islamic schools.